2015
DOI: 10.1007/s11655-015-2287-y
|View full text |Cite
|
Sign up to set email alerts
|

Is the Chinese medicinal formula Guipi Decoction (归脾汤) effective as an adjunctive treatment for depression? A meta-analysis of randomized controlled trials

Abstract: The fifindings of this meta-analysis were in keeping with the notion that GPD formulations were effective in the treatment of depression without causing any serious adverse effects. However, currently available evidence was of low quality and therefore inadequate to justify a strong recommendation of using GPD formulations in the management of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…However, despite the safety of the administered mixture which was tested, the preparation method was not detailed [ 135 ]. In traditional Chinese medicine, the Guilpi decoction, an herbal mixture, is used given its ability to regulate blood pressure and as an antidepressant [ 136 ]. So, Zhuang et al [ 137 ] tested the effect of Guilpi decoction in 120 elderly patients affected with hypertension and depression.…”
Section: Health-promoting Effects: Data From Clinical Findingsmentioning
confidence: 99%
“…However, despite the safety of the administered mixture which was tested, the preparation method was not detailed [ 135 ]. In traditional Chinese medicine, the Guilpi decoction, an herbal mixture, is used given its ability to regulate blood pressure and as an antidepressant [ 136 ]. So, Zhuang et al [ 137 ] tested the effect of Guilpi decoction in 120 elderly patients affected with hypertension and depression.…”
Section: Health-promoting Effects: Data From Clinical Findingsmentioning
confidence: 99%
“…Xiao Chai Hu decoction can promote the recovery of BDNF levels, improve levels of neurofunctional factors, and enhance sleep quality. 147,148 Other formulas, such as Baihe Dihuang decoction, can significantly increase the content of dopamine and serotonin in the cerebral cortex, hypothalamus, hippocampus, and striatum of rats; 149 Guipi decoction increases the levels of serotonin, NE, and dopamine in the hippocampus; 150 and Xuefu Zhuyu decoction can significantly increase serotonin concentration and promote the expression of serotonin-1A receptors. 151 These formulas also have ideal therapeutic antidepressant effects.…”
Section: The Pharmacological Mechanism Of Jzg In the Treatment Of Depmentioning
confidence: 99%
“…A study demonstrated that GPT exerts no acute or genotoxic effects on rats and is hence safe ( Park et al., 2014 ). Clinically, GPT improves symptoms of anxiety and life quality in elderly depression patients, which was later proven by a meta-analysis of randomized controlled trials ( Sheng et al., 2017 ; Li et al., 2014 ). In addition, use a combination of GPT and antidepressants significantly ameliorate the symptoms of depression and increase the rates of effectiveness and recovery compared with antidepressant therapy alone ( Sheng et al., 2017 ).…”
Section: Introductionmentioning
confidence: 96%